Pre‐initiation complex assembly functions as a molecular switch that splits the Mcm2‐7 double hexamer. (17th August 2017) - Miyazawa‐Onami, Mayumi; Araki, Hiroyuki; Tanaka, Seiji
Abstract: Initiation of chromosomal DNA replication in eukaryotes involves two steps: licensing and firing. In licensing, a core component of the replicative helicase, the Mcm2–7 complex, is loaded onto replication origins as an inactive double hexamer, which is activated in the firing step by firing factors. A reaction intermediate called the pre‐initiation complex (pre‐IC) has been proposed to assemble transiently during firing, but the existence of the pre‐IC has not yet been confirmed. Here, we show, by systematic chromatin immunoprecipitation, that a distinct intermediate that fits the definition of the pre‐IC assembles during firing in the budding yeast Saccharomyces cerevisiae . Pre‐IC assembly is observed in the absence of Mcm10, one of the firing factors, and is mutually dependent on all the firing factors whose association to replication origins is triggered by cyclin‐dependent kinase. In the pre‐IC, the Mcm2–7 double hexamer is separated into single hexamers, as in the active helicase. Our data indicate that pre‐IC assembly functions as an all‐or‐nothing molecular switch that splits the Mcm2–7 double hexamer. Synopsis: This study reveals how the pre‐initiation complex (pre‐IC) during DNA replication initiation is assembled, and shows that pre‐IC assembly separates the core component of the replicative helicase, the Mcm2–7 double hexamer. All firing factors associate with replication origins to assemble pre‐IC before Mcm10 functions. Pre‐IC assembly is mutually dependent on all the firing factors whose association with replication origins is triggered by CDK. In the pre‐IC, not only the formation of tight Cdc45‐Mcm2–7‐GINS (CMG) complex, but also the separation of Mcm2–7 double hexamer occurs. Abstract : This study reveals how the pre‐initiation complex (pre‐IC) during DNA replication initiation is assembled, and shows that pre‐IC assembly separates the core component of the replicative helicase, the Mcm2–7 double hexamer.